Order Blattodea Brunner von Wattenwyl, 1882. In: Zhang, Z.-Q. (Ed.) Animal biodiversity: An outline of higher-level classification and survey of taxonomic richness - Beccaloni, George W.; Eggleton, Paul (Zootaxa, 2011)
-